Iron-chromium-aluminum alloy powder, preparation method and iron-chromium-aluminum electrothermal alloy material
Through vacuum smelting and aerosol powder, carbon nitride and oxide dispersion strengthening iron-chromium aluminum alloy powder is formed, solving the problems of grain growth, low high temperature strength and easy oxide scale peeling in high temperature service, achieving consistent improvement of high temperature tissue stability and performance.
Patent Information
- Application Number
- CN202411805827.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
After serving at high temperature, iron-chromium aluminum alloys have problems such as grain growth, low high temperature strength and easy peeling of oxide scales, which affects their application in nuclear power and harmful gas purification.
By melting the alloy raw material under vacuum and using a mixture of argon, oxygen and nitrogen as atomization and powdering to form a carbon nitride and oxide dispersion-strengthening iron-chromium aluminum alloy powder, then iron-chromium aluminum electrothermal alloy material is prepared by thermal isostatic densification.
It significantly improves the high-temperature structure stability, high-temperature strength and oxidation resistance of iron-chromium aluminum alloy, extends its high-temperature service life, and improves the consistency of performance.
Smart Images

Figure CN119615002A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of alloy technology, and in particular to an iron-chromium-aluminum alloy powder and a preparation method thereof, and an iron-chromium-aluminum electric heating alloy material. Background Art
[0002] Iron-chromium-aluminum alloy has excellent high-temperature oxidation resistance, good corrosion resistance and high-temperature service stability, and has broad application prospects in nuclear power, harmful gas purification and porous materials. As an important electrothermal alloy material, the maximum operating temperature of iron-chromium-aluminum alloy can reach 1400℃, but it still has shortcomings such as grain growth after ultra-high temperature service, low high-temperature strength and easy peeling of oxide scale. In response to the above shortcomings, researchers have developed an oxide dispersion strengthened iron-chromium-aluminum (ODS-FeCrAl) alloy prepared by powder metallurgy. The high-temperature organizational stability, high-temperature strength and high-temperature oxidation resistance of this material have been significantly improved.
[0003] There are two main preparation methods for ODS-FeCrAl alloy: mechanical alloying and atomization powder making. Mechanical alloying is to prepare ODS-FeCrAl alloy by mechanically grinding oxide and metal powder, and then hot isostatic pressing the ground mixed powder. This process has a small single powder production amount, low efficiency and poor material consistency, which is not conducive to mass production. The atomization powder making technology is to atomize the molten metal liquid into fine droplets through high-speed airflow, and then quickly solidify it into metal powder, and finally prepare a dense block product through hot isostatic pressing technology. Domestic and foreign researchers have added oxidizing gas to the atomizing airflow through various means to produce oxides on the surface of the alloy powder, so as to achieve the purpose of atomizing and oxygenating the alloy powder, and prepare oxide-dispersion-strengthened iron-chromium-aluminum electrothermal alloy. The preparation method of adding oxidizing gas during the atomization process solves the problem of mechanical alloying being difficult to mass produce, but there are still disadvantages such as uneven distribution of oxide particles, unstable size, large regional oxygen content differences, and poor consistency in high-temperature service after single oxide strengthening, which causes local deformation / melting of ODS-FeCrAl electric heating alloy wire or strip during high-temperature service, affecting the service life of electric heating alloy components. Therefore, how to improve the high-temperature service performance of Fe-Cr-Al alloy is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The present application provides an iron-chromium-aluminum alloy powder and a preparation method, and an iron-chromium-aluminum electric heating alloy material to solve the following technical problem: how to improve the high-temperature service performance of the iron-chromium-aluminum alloy.
[0005] In a first aspect, the present application provides an iron-chromium-aluminum alloy powder, wherein the chemical composition of the iron-chromium-aluminum alloy powder includes, by mass fraction: C: 0.01%-0.05%, Cr: 13%-25%, Al: 4%-7%, Si: 0.01%-1%, Mn: 0.01%-1%, Ti>0 and ≤1.5%, Zr: 0.01%-0.2%, W: 0.01%-0.1%, Mo>0 and ≤3%, V: 0.01%-0.1%, Ta: 0.01%-0.3%, Nb: 0.01%-1%, Y: 0.01%-0.2%, Hf: 0.01%-0.2%, O: 0.04%-0.1%, N: 0.01%-0.03% and Fe.
[0006] Optionally, the iron-chromium-aluminum alloy powder is dispersed with carbides, nitrides and oxides.
[0007] Optionally, the carbide and nitride exist in the form of carbonitride, the average size of the carbonitride is 40 nm to 60 nm, and the carbonitride includes (Ti, Nb)(C, N).
[0008] Optionally, the average size of the oxide is 5 nm to 15 nm, and the oxide includes (Al, Y) 2 O 3 .
[0009] Optionally, the average particle size of the iron-chromium-aluminum alloy powder is 20 μm to 30 μm.
[0010] In a second aspect, the present application provides a method for preparing the iron-chromium-aluminum alloy powder according to any one embodiment of the first aspect, the method comprising:
[0011] Under vacuum conditions, the alloy raw materials are melted into a liquid state to obtain a liquid alloy;
[0012] A mixed gas of argon, oxygen and nitrogen is used as an atomizing gas to atomize and powder the liquid alloy to obtain an iron-chromium-aluminum alloy powder.
[0013] Optionally, in the mixed gas, the oxygen accounts for 1% to 20%, the nitrogen accounts for 1% to 10%, and the argon accounts for 70% to 98%, calculated by volume fraction.
[0014] Optionally, the flow rate of the atomizing gas is 1200 Nm 3 / h~1400Nm 3 / h.
[0015] Optionally, the smelting temperature is 1550°C to 1600°C, and the smelting time is 30min to 90min.
[0016] In a third aspect, the present application provides an iron-chromium-aluminum electrothermal alloy material, wherein the iron-chromium-aluminum electrothermal alloy material is obtained by densifying the iron-chromium-aluminum alloy powder according to any one of the first aspects through hot isostatic pressing, and the iron-chromium-aluminum electrothermal alloy material satisfies at least one of the following properties:
[0017] High temperature strength at 900℃≥42MPa;
[0018] High temperature strength at 1000℃≥35MPa;
[0019] Rapid life at 1350℃≥100h;
[0020] The maximum operating temperature is 1425℃.
[0021] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0022] The present application provides an iron-chromium-aluminum alloy powder, wherein the chemical composition of the iron-chromium-aluminum alloy powder includes, by mass fraction, C: 0.01% to 0.05%, Cr: 13% to 25%, Al: 4% to 7%, Si: 0.01% to 1%, Mn: 0.01% to 1%, Ti>0 and ≤1.5%, Zr: 0.01% to 0.2%, W: 0.01% to 0.1%, Mo>0 and ≤3%, V: 0.01% to 0.1%, Ta: 0.01% to 0.3%, Nb: 0.01% to 1%, Y: 0.01% to 0.2%, Hf: 0.01% to 0.2%, O: 0.04% to 0.1%, N: 0.01% to 0.03% and Fe. The present application rationally designs the chemical composition of the iron-chromium-aluminum alloy powder. Elements such as W, Mo, V, Al, Ta, Nb, Hf, Ti, and Zr combine with nitrogen and carbon in the atomizing atmosphere to form fine carbonitrides; Al, Ti, Y, and Zr elements can react with oxygen in the atomizing atmosphere to form oxides to play a dispersion strengthening role, thereby obtaining an alloy with higher organizational stability and better performance consistency, thereby improving the high-temperature service performance of Fe-Cr-Al alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0025] Figure 1A schematic flow chart of a method for preparing an iron-chromium-aluminum alloy powder provided in an embodiment of the present application;
[0026] Figure 2 This is a surface morphology of the iron-chromium-aluminum alloy powder provided in Example 1 of the present application;
[0027] Figure 3 This is a morphology diagram of carbon, nitrogen and oxides of the iron-chromium-aluminum electric heating alloy material provided in Example 1 of the present application. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0029] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0030] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "the following at least one item (items)" or similar expressions refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple. "Parts" such as parts by weight and parts by mass indicate the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, the mass ratio of substance A, substance B, and substance C is 1:2:3, then substance A, substance B, and substance C should correspond one-to-one with the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.
[0031] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0032] The present application provides an iron-chromium-aluminum alloy powder, and the chemical composition of the iron-chromium-aluminum alloy powder includes, by mass fraction: C: 0.01%-0.05%, Cr: 13%-25%, Al: 4%-7%, Si: 0.01%-1%, Mn: 0.01%-1%, Ti>0 and ≤1.5%, Zr: 0.01%-0.2%, W: 0.01%-0.1%, Mo>0 and ≤3%, V: 0.01%-0.1%, Ta: 0.01%-0.3%, Nb: 0.01%-1%, Y: 0.01%-0.2%, Hf: 0.01%-0.2%, O: 0.04%-0.1%, N: 0.01%-0.03% and Fe.
[0033] The present application rationally designs the chemical composition of the iron-chromium-aluminum alloy powder. Elements such as W, Mo, V, Al, Ta, Nb, Hf, Ti, and Zr combine with nitrogen and carbon in the atomization atmosphere to generate fine carbonitrides; Al, Ti, Y, and Zr elements can react with oxygen in the atomization atmosphere to generate oxides to play a role in dispersion strengthening, thereby obtaining an alloy with higher organizational stability and better performance consistency. The specific chemical composition functions are as follows:
[0034] Fe: As the main component of the alloy, it provides basic mechanical properties and electrical conductivity. Cr: Improves the corrosion resistance, oxidation resistance and high temperature strength of the alloy. Al: Enhances the oxidation resistance and high temperature stability of the alloy, and reacts with oxygen to form oxides, which plays a role in dispersion strengthening. W, Mo, V: These elements combine with nitrogen and carbon during the atomization process to form fine carbonitrides, which improve the high temperature strength and wear resistance of the alloy. Ta, Nb: They also form carbonitrides, but their addition may also improve the plasticity and toughness of the alloy. Ti, Zr, Hf: In addition to forming carbonitrides, these elements can also react with oxygen to form oxides, further dispersion strengthening the alloy. Y: As a rare earth element, it helps to refine the grains and improve the toughness and fatigue resistance of the alloy. Si, Mn: As auxiliary elements, they may help to improve the strength and toughness of the alloy. C, N, O: These elements react with alloying elements during the gas atomization process to form carbonitrides and oxides.For example, the C content may be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, etc., the Cr content may be 13%, 14%, 16%, 18%, 20%, 22%, 24%, 25%, etc., the Al content may be 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, etc., the Si content may be 0.01%, 0.05%, 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1%, etc., and the Mn content may be 0.01%. , 0.05%, 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1%, etc., the Ti content can be 0.01%, 0.05%, 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.2%, 1.5%, etc., the Zr content can be 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, etc., the W content can be 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, etc., and the Mo content can be 0. The content of V can be 0.01%, 0.03%, 0.05%, 0.07%, 0.09%, 0.1%, etc. The content of Ta can be 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, etc. The content of Nb can be 0.01%, 0.02%, 0.03%, 0.04%, 0.06%, 0.08%, 1%, etc. The content of Y can be 0. The content of Hf can be 0.01%, 0.05%, 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, etc. The content of O can be 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, etc. The content of N can be 0.01%, 0.015%, 0.02%, 0.025%, 0.03%, etc.
[0035] Fe is a matrix element. The specific content / content range of Fe can be obtained through the upper and lower limit formulas of the components, that is, the sum of the percentages of the contents of each component in a composition should be equal to 100%, and the content ranges of several components should meet the following conditions: the upper limit value of a component + the lower limit values of other components ≤ 100; the lower limit value of a component + the upper limit values of other components ≥ 100.
[0036] In some embodiments, the iron-chromium-aluminum alloy powder is dispersed with carbides, nitrides and oxides.
[0037] In some embodiments, the carbide and nitride exist in the form of carbonitride, the average size of the carbonitride is 40 nm to 60 nm, and the carbonitride includes (Ti, Nb)(C, N).
[0038] In some embodiments, the average size of the oxide is 5 nm to 15 nm, and the oxide includes (Al, Y) 2 O 3 .
[0039] By adding a variety of microalloying elements such as Ti, Zr, Mo, V, Ta, W, Hf and Nb, a multi-component carbonitride with small size and dispersed distribution is formed during the atomization process. Compared with the simple component carbonitride formed by traditional smelting, it has the advantages of good high-temperature stability and high strengthening effect. In addition, a large number of dispersed oxides can be formed during the atomization process. This iron-chromium-aluminum electrothermal alloy material strengthened by carbide / nitride / oxide composite dispersion makes up for the disadvantage of uneven distribution of ODS-FeCrAl oxides. At the same time, adding a variety of microalloying elements can obtain a multi-component carbonitride with small size during the atomization process. Compared with the carbonitride precipitated by traditional metallurgical methods, it has higher high-temperature stability. Therefore, the iron-chromium-aluminum electrothermal alloy material has higher organizational stability and better performance consistency at high temperatures, and has the application potential of mass production. Exemplarily, the average size of the carbonitrides may be 40 nm, 42 nm, 45 nm, 50 nm, 52 nm, 55 nm, 58 nm, 60 nm, etc., and the average size of the oxides may be 5 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 15 nm, etc.
[0040] In some embodiments, the average particle size of the iron-chromium-aluminum alloy powder is 20 μm to 30 μm.
[0041] The average particle size of the iron-chromium-aluminum alloy powder is limited to 20 μm to 30 μm, and the gaps between the powder particles are reduced, which is conducive to achieving tighter stacking and bonding during the hot isostatic pressing process, thereby improving the density of the block product. For example, the average particle size of the iron-chromium-aluminum alloy powder can be 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, etc.
[0042] Figure 1 A schematic flow chart of a method for preparing an iron-chromium-aluminum alloy powder provided in an embodiment of the present application.
[0043] Based on a general inventive concept, see Figure 1 The present application provides a method for preparing the iron-chromium-aluminum alloy powder described in any one of the above embodiments, the method comprising:
[0044] S1. Under vacuum conditions, melting the alloy raw materials into a liquid state to obtain a liquid alloy;
[0045] In some embodiments, the vacuum degree of the smelting is ≤1Pa.
[0046] The melting is carried out under vacuum conditions, and the vacuum degree is controlled at ≤1Pa to eliminate the influence of oxygen and other impurities on the alloy.
[0047] In some embodiments, the smelting temperature is 1550° C. to 1600° C., and the smelting time is 30 min to 90 min.
[0048] The melting temperature is set at 1550°C to 1600°C to ensure that the alloy raw materials can be completely melted and evenly mixed. The melting time is controlled at 30min to 90min to ensure the uniformity and stability of the alloy composition. Exemplarily, the melting temperature can be 1550°C, 1560°C, 1570°C, 1580°C, 1590°C, 1600°C, etc., and the melting time can be 30min, 40min, 50min, 60min, 70min, 80min, 90min, etc.
[0049] S2. Using a mixture of argon, oxygen and nitrogen as an atomizing gas, the liquid alloy is atomized and powdered to obtain an iron-chromium-aluminum alloy powder.
[0050] Atomization is the process in which liquid alloy is rapidly atomized into fine powder particles under the action of high-pressure gas.
[0051] In some embodiments, in the mixed gas, the oxygen accounts for 1% to 20%, the nitrogen accounts for 1% to 10%, and the argon accounts for 70% to 98%, calculated by volume fraction.
[0052] Limiting the proportion of oxygen to 1% to 20% helps to form a stable oxide film during the atomization process, and these oxide films can further improve the oxidation resistance of the alloy. At the same time, oxygen can also react with certain elements in the alloy (such as aluminum) to form oxides. Limiting the proportion of nitrogen to 1% to 10%, nitrogen can react with elements such as titanium and niobium in the alloy to form nitrides, which also have the effect of dispersion strengthening. The addition of nitrogen can also adjust the gas atmosphere during the atomization process, which helps to form finer and more uniform powder particles. Limiting the proportion of argon to 70% to 98%, argon is an inert gas and is mainly used to protect the alloy from air oxidation and contamination during the atomization process. At the same time, argon can also be used as the main atomizing gas to form fine alloy powders through high-speed injection. Exemplarily, the proportion of oxygen can be 1%, 3%, 5%, 10%, 15%, 18%, 20%, etc., the proportion of nitrogen can be 1%, 3%, 5%, 7%, 9%, 10%, etc., and the proportion of argon can be 70%, 75%, 80%, 90%, 95%, 98%, etc.
[0053] In some embodiments, the flow rate of the atomizing gas is 1200 Nm 3 / h~1400Nm 3 / h.
[0054] The flow rate of atomizing gas is controlled at 1200Nm 3 / h~1400Nm 3 / h to ensure that the liquid alloy can be fully atomized and form fine powder particles. For example, the flow rate of the atomizing gas can be 1200Nm 3 / h、1250Nm 3 / h、1300Nm 3 / h、1350Nm 3 / h、1400Nm 3 / h, etc.
[0055] The product prepared by the method for preparing the iron-chromium-aluminum alloy powder is the above-mentioned iron-chromium-aluminum alloy powder. The chemical composition and microstructure of the iron-chromium-aluminum alloy powder prepared by the method for preparing the iron-chromium-aluminum alloy powder can refer to the above-mentioned embodiment. Since the method for preparing the iron-chromium-aluminum alloy powder adopts part or all of the technical solutions of the iron-chromium-aluminum alloy powder embodiment, it at least has all the beneficial effects brought by the technical solutions of the iron-chromium-aluminum alloy powder embodiment, which will not be described one by one here.
[0056] The present application provides an iron-chromium-aluminum electrothermal alloy material, wherein the iron-chromium-aluminum electrothermal alloy material is prepared by densifying the iron-chromium-aluminum alloy powder according to any one of the first aspects through hot isostatic pressing, and the iron-chromium-aluminum electrothermal alloy material satisfies at least one of the following properties:
[0057] High temperature strength at 900℃≥42MPa;
[0058] High temperature strength at 1000℃≥35MPa;
[0059] Rapid life at 1350℃≥100h;
[0060] The maximum operating temperature is 1425℃.
[0061] The present application prepares a carbide / nitride / oxide dispersion-strengthened iron-chromium-aluminum electric heating alloy material, which overcomes the disadvantage of inconsistent oxide distribution characteristics in traditional alloys. At the same time, adding a variety of micro-alloying elements can obtain multi-component carbonitrides with small sizes during the atomization process, which have higher high-temperature stability than carbonitrides precipitated by traditional metallurgical methods.
[0062] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0063] Example 1
[0064] The mass percentage of each component in the alloy raw material is Cr: 18%, Al: 5%, Y: 0.18%, Ti: 0.05%, Zr: 0.05%, Mn: 0.5%, Si: 0.5%, Mo: 1.9%, W: 0.06%, V: 0.03%, Ta: 0.1%, Nb: 0.3%, Hf: 0.06%, C: 0.03%, and the rest is Fe. Vacuum melting is adopted, the vacuum degree is 1Pa, the melting temperature is 1570℃, and the melting time is 60min. After melting, argon gas is filled into the entire device for protection. Gas atomization powder making is started, and the atomizing gas is a mixture of argon, nitrogen and oxygen containing 10vol% oxygen and 10vol% nitrogen, and the flow rate of the atomizing gas is 1200Nm 3 / h to obtain iron-chromium-aluminum alloy powder.
[0065] The oxygen content of the obtained powder is 0.06%, and the nitrogen content is 0.03%. After densification by hot isostatic pressing, the obtained iron-chromium-aluminum electrothermal alloy material has a high-temperature tensile property of 43MPa at 900°C, a high-temperature tensile property of 36MPa at 1000°C, and a rapid life of 128h at 1350°C. It has excellent high-temperature service performance and can be used at ultra-high temperatures up to 1425°C.
[0066] Figure 2 This is a surface morphology of the iron-chromium-aluminum alloy powder provided in Example 1 of the present application. Figure 2 It can be seen that the particles of the Fe-Cr-Al alloy powder are evenly distributed and the average particle size is 25 μm.
[0067] Figure 3 This is a morphology of carbon, nitrogen and oxides of the iron-chromium-aluminum electric heating alloy material provided in Example 1 of the present application. Figure 3 It can be seen that the Fe-Cr-Al electric heating alloy material contains a large amount of carbides, nitrides and oxides at the same time, among which the average size of carbonitrides is 50nm and the average size of oxides is 10nm.
[0068] Example 2
[0069] The mass percentage of each component in the alloy raw material is Cr: 20%, Al: 5.5%, Y: 0.15%, Ti: 0.15%, Zr: 0.1%, Mn: 0.5%, Si: 0.5%, Mo: 1.9%, W: 0.06%, V: 0.03%, Ta: 0.1%, Nb: 0.3%, Hf: 0.06%, C: 0.03% and the rest is Fe. Vacuum melting is adopted, the vacuum degree is 1Pa, the melting temperature is 1570℃, and the melting time is 60min. After melting, argon gas is filled into the whole device for protection. Gas atomization powder making is started, and the atomizing gas is a mixture of argon, nitrogen and oxygen containing 10vol% oxygen and 7vol% nitrogen, and the flow rate of the atomizing gas is 1300Nm 3 / h to obtain iron-chromium-aluminum alloy powder.
[0070] The oxygen content of the obtained powder is 0.06%, and the nitrogen content is 0.02%. After densification by hot isostatic pressing, the obtained iron-chromium-aluminum electrothermal alloy material has a high-temperature tensile property of 45MPa at 900°C, a high-temperature tensile property of 38MPa at 1000°C, and a fast life of 112h at 1350°C. It has excellent high-temperature service performance and can be used at ultra-high temperatures up to 1425°C.
[0071] Example 3
[0072] The mass percentage of each component in the alloy raw material is Cr: 23%, Al: 5.8%, Y: 0.05%, Ti: 1.2%, Zr: 0.2%, Mn: 0.5%, Si: 0.5%, Mo: 1.9%, W: 0.06%, V: 0.03%, Ta: 0.1%, Nb: 0.3%, Hf: 0.06%, C: 0.03% and the rest is Fe. Vacuum melting is adopted, the vacuum degree is 1Pa, the melting temperature is 1570℃, and the melting time is 60min. After melting, argon gas is filled into the whole device for protection. Gas atomization powder making is started, and the atomizing gas is a mixture of argon, nitrogen and oxygen containing 10vol% oxygen and 3vol% nitrogen, and the flow rate of the atomizing gas is 1400Nm 3 / h to obtain iron-chromium-aluminum alloy powder.
[0073] The oxygen content of the obtained powder is 0.06%, and the nitrogen content is 0.005%. After densification by hot isostatic pressing, the obtained iron-chromium-aluminum electrothermal alloy material has a high-temperature tensile property of 42MPa at 900°C, a high-temperature tensile property of 35MPa at 1000°C, and a fast life of 104h at 1350°C. It has excellent high-temperature service performance and can be used at ultra-high temperatures up to 1425°C.
[0074] Comparative Example 1
[0075] This comparative example is further modified as follows based on the contents disclosed in Example 1:
[0076] The atomizing gas is only oxygen and argon, and does not contain nitrogen. The atomizing gas contains 10 vol% oxygen, and the remainder is argon.
[0077] The nitrogen content of the iron-chromium-aluminum alloy powder obtained in Comparative Example 1 is 0.003%. After densification by hot isostatic pressing, the obtained iron-chromium-aluminum electrothermal alloy material has a high-temperature tensile property of 35 MPa at 900°C, a high-temperature tensile property of 23 MPa at 1000°C, and a fast life of 98 h at 1350°C.
[0078] Comparative Example 2
[0079] This comparative example is further modified as follows based on the contents disclosed in Example 1:
[0080] It does not contain Ti, Zr and Nb elements.
[0081] After the iron-chromium-aluminum alloy powder obtained in Comparative Example 2 was densified by hot isostatic pressing, the obtained iron-chromium-aluminum electrothermal alloy material had a high-temperature tensile property of 30 MPa at 900°C, a high-temperature tensile property of 25 MPa at 1000°C, and a fast life of 46 h at 1350°C.
[0082] Comparative Example 3
[0083] This comparative example is further modified as follows based on the contents disclosed in Example 1:
[0084] The contents of Ti, Zr and Nb elements are low, with Ti content being 0.02%, Zr content being 0.007% and Nb content being 0.008%.
[0085] After the iron-chromium-aluminum alloy powder obtained in Comparative Example 3 was densified by hot isostatic pressing, the obtained iron-chromium-aluminum electrothermal alloy material had a high-temperature tensile property of 32 MPa at 900°C, a high-temperature tensile property of 26 MPa at 1000°C, and a fast life of 76 h at 1350°C.
[0086] In addition, one or more technical solutions in the embodiments of the present application have at least the following technical effects or advantages:
[0087] In the embodiments of the present application, compared with the traditional iron-chromium-aluminum alloy powder, the iron-chromium-aluminum alloy powder has a carbide / nitride / oxide composite dispersion strengthening structure formed during the atomization process, which makes the oxide distribution more uniform, thereby helping to improve the overall performance and stability of the alloy.
[0088] In the embodiment of the present application, due to the presence of multi-component carbonitrides and oxides, the iron-chromium-aluminum electric heating alloy material can still maintain excellent stability and performance at high temperatures. At the same time, the dispersed carbonitrides and oxides can significantly improve the strength and hardness of the alloy, making it have better wear resistance and corrosion resistance. The iron-chromium-aluminum electric heating alloy material has higher organizational stability and better performance consistency at high temperatures, and has application potential for mass production.
[0089] In the embodiments of the present application, the alloy is prepared by an advanced process combining vacuum melting and gas atomization, thereby ensuring the stability and consistency of the alloy composition and obtaining fine and uniform powder particles.
[0090] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. An iron-chromium-aluminum alloy powder, wherein the chemical composition of the iron-chromium-aluminum alloy powder comprises, by mass fraction: C: 0.01%~0.05%, Cr: 13%~25%, Al: 4%~7%, Si: 0.01%~1%, Mn: 0.01%~1%, Ti>0 and ≤1.5%, Zr: 0.01%~0.2%, W: 0.01%~0.1%, Mo>0 and ≤3%, V: 0.01%~0.1%, Ta: 0.01%~0.3%, Nb: 0.01%~1%, Y: 0.01%~0.2%, Hf: 0.01%~0.2%, O: 0.04%~0.1%, N: 0.01%~0.03% and Fe.
2. The iron-chromium-aluminum alloy powder according to claim 1, characterized in that The iron-chromium-aluminum alloy powder is dispersed with carbides, nitrides and oxides.
3. The iron-chromium-aluminum alloy powder according to claim 2, characterized in that: The carbide and nitride exist in the form of carbonitride, the average size of the carbonitride is 40nm-60nm, and the carbonitride includes (Ti, Nb)(C, N).
4. The iron-chromium-aluminum alloy powder according to claim 2, characterized in that: The average size of the oxide is 5 nm to 15 nm, and the oxide includes (Al, Y) 2 O 3 .
5. The iron-chromium-aluminum alloy powder according to claim 2, characterized in that: The average particle size of the iron-chromium-aluminum alloy powder is 20 μm to 30 μm.
6. A method for preparing the iron-chromium-aluminum alloy powder according to any one of claims 1 to 5, the method comprising: Under vacuum conditions, the alloy raw materials are melted into a liquid state to obtain a liquid alloy; A mixed gas of argon, oxygen and nitrogen is used as an atomizing gas to atomize and powder the liquid alloy to obtain an iron-chromium-aluminum alloy powder.
7. The method according to claim 7, characterized in that In terms of volume fraction, in the mixed gas, the oxygen accounts for 1% to 20%, the nitrogen accounts for 1% to 10%, and the argon accounts for 70% to 98%.
8. The method according to claim 7, characterized in that The flow rate of the atomizing gas is 1200 Nm 3 / h~1400Nm 3 / h.
9. The method according to claim 7, characterized in that The smelting temperature is 1550° C. to 1600° C., and the smelting time is 30 min to 90 min.
10. An iron-chromium-aluminum electrothermal alloy material, wherein the iron-chromium-aluminum electrothermal alloy material is obtained by densifying the iron-chromium-aluminum alloy powder according to any one of claims 1 to 5 through hot isostatic pressing, and the iron-chromium-aluminum electrothermal alloy material satisfies at least one of the following properties: High temperature strength at 900℃≥42MPa; High temperature strength at 1000℃≥35MPa; Rapid life at 1350℃≥100h; The maximum operating temperature is 1425℃.